Corporate Governance Toward Sustainability Disclosure: Recent Development and Future Research Agenda - Dewi, Luh Gede Krisna; Wiagustini, Ni Luh Putu; Rahyuda, Henny; Sudana, I Putu (Jurnal Ilmiah Akuntansi dan Bisnis, 2022)
The concept of sustainability is important in global business practices. Companies should manage business practices that are in line with the achievement of the SDGs agenda. This study aims to review previous research and fill gaps using a literature review approach. It critically reviews the theoretical perspectives and issues based on the relationship between corporate governance mechanisms and the level of corporate sustainability disclosure. This study adopts a systematic literature review approach with bibliometric analysis methods and content analysis using 44 articles from the Scopus database. The results of this study describe three clusters in the latest research developments. The first cluster is with regard to corporate social responsibility, the second is board composition; and the third is practical implications. Another finding is female director and independent director variables appear to be predictors of the sustainability report disclosure. The implication of the research is to provide comprehensive future research agenda. Keywords : corporate governance, sustainability disclosure, board composition, bibliometric analysis